Social Network Analysis to Examine the Effectiveness of e-PBL with Design Thinking to Foster Collaboration: Comparisons between High and Low Self-regulated Learners - Nordin, Norfarah; Samsudin, Mohd Ali; Mansor, Aizul Fared; Ismail, Mohd Erfy (Journal of Technical Education and Training, 2020)
In TVET teaching and learning, learners’ collaboration is important to ensure learning effectiveness. However, employing either design thinking or online problem-based learning would not lead to fruitarian. Hence, to devise teaching and learning that employs design thinking (DT) and online problem-based learning (ePBL) pedagogies used in tandem with social media learning environment in Facebook are hypothesized to improve TVET learner’s collaboration. By adopting the Social Constructivism learning theory that social interaction fosters collaborative learning and build learners’ knowledge and understanding, this study is commenced. Social interaction that fosters learners’ collaboration is moderated by type of learners’ self-regulation (SR) towards learning. Previous research hypothesized that ePBL alone only worked effectively for high self-regulated learners. The learning outcome inequity present due to the pedagogy limitation. This research devises ePBL with DT as a combination of pedagogies that benefits the low SR learners as well. To monitor collaborative learning occurrences, network ties via social media footprints of individual TVET learners is tracked from the learners’ Facebook group. The effectiveness of treatments is monitored using social network analysis i.e. graph theory and centrality concept employing NodeXL software. Samples of 142 TVET pre-service teachers that currently enroll in Design and Technology course at Teachers’ Training Institutes in Malaysia participated in this study. The samples are intact group and classified into high-SR learners and low-SR learners. Social network analysis using Vertices index, Geodesic distance and graph visualization findings show that ePBL with DT works in fostering learning collaboration for both high-SR and low-SR learners. This implies that national e-learning policy and ePBL embeddedness into technical subject is promising, regardless of the type of learners provided that DT is incorporated into the pedagogy.